Local community participation in mining in Finnish Lapland and Northern British Columbia, Canada – Practical applications of CSR and SLO. (June 2019) - Tuulentie, Seija; Halseth, Greg; Kietäväinen, Asta; Ryser, Laura; Similä, Jukka
Highlights: Social issues have ever-increasing importance in mining industry. SLO and CSR have similar aims from slightly different angles. Arranging communication between communities and companies should be obligatory. Binding agreements between companies and communities demand clear definitions.